3
$\begingroup$

I would like to prove

$\{ \neg N,\neg N \to L,D \leftrightarrow \neg N \} \vdash (L \lor A) \land D $.

My work until now is as follows: $$ \begin{array}{l|ll} 1 & \neg N & \text{Premise} \\ 2 & (\neg N \to L) \land (D \leftrightarrow \neg N) & \text{Premise} \\ 3 & \vdash (L \lor A) \wedge D & \text{Premise} \\ 4 & \neg N \to L & \text{$ \land $-Elimination from $ 2 $} \\ 5 & (D \leftrightarrow \neg N) & \text{$ \land $-Elimination from $ 2 $ and $ 4 $} \end{array} $$ What’s next? This is where I’ve been for the past $ 3 $ hours. Help me out if you can, and please suggest me books for Logic and Natural Deduction.

Thanks.

$\endgroup$
3
$\begingroup$

The conclusion is not a premise.   You can't use it to prove itself; that's circular reasoning.   Circular reasoning is bad because circular reasoning is bad.

$$\begin{array}{r|ll} 1- & ¬N &\text{Premise} \\ 2- & (¬N → L) \wedge (D ↔ ¬N) &\text{Premise} \\ 3- & ¬N → L &\wedge \text{ Elimination from }2 \\ 4- & & \text{Modus Ponens from }1, 3 \\ 5- & & \vee \text{ Introduction from }4 \\ 6- & (D ↔ ¬N) & \wedge \text{ Elimination from }2 \\ 7- & (D\to \neg N)\wedge (\neg N \to D) & \text{Equivalent restatement of }6 \\ 8- & & \wedge \text{ Elimination from }7 \\ 9- & & \text{Modus Ponens from }1, 8 \\ 10 - & (L\vee A)\wedge D & \wedge \text{ Introduction of }5, 9 \\ \hline \therefore & \{\neg N, (\neg N\to L)\wedge (D\leftrightarrow \neg N)\}\vdash (L\vee A)\wedge D & \Box \end{array} $$

Can you fill in the blanks?

$\endgroup$
2
$\begingroup$

As complement to the answer above, I would suggest you to begin with:

  • Hodges & Chirswell's Mathematical Logic (2007) - The very book begin by taking an informal exposal of natural deduction in Chapter 2 before they got more serious on the subject taking the propositional (p.53) and first-order calculus (p.177)

After you get some feeling of it, maybe you would like to take a look at:

  • Van Dalen's Logic and Structure (2004) - See p.30 for the propopositional logic and p.91 for first-order calculus. Van Dalen's exposition seems more rigorous, which is why maybe is better to read his book after having some previous knowledge first.

You can also take a look at Peter Smith's wonderful study guide, Teach Yourself Logic.

$\endgroup$
0
$\begingroup$

Here is what the OP would like to prove:

{¬N,¬N→L,D↔¬N}⊢(L∨A)∧D

The attempt, however, combines premises 2 and 3 into one conjunction. It is best to copy the premises as they are into the first lines of the proof.

The OP would also like the following:

...please suggest me books for Logic and Natural Deduction.

The following proof uses the proof checker associated with the forallx Calgary Remix: An Introduction to Formal Logic text. This is a beginning truth-functional and first-order logic textbook. See links below. They may complement the references provided by Bruno Bentzen or what you are using now.

Here is the proof using that proof checker:

enter image description here

Here is the proof in words:

  • The first premise allows us to derive $L$ from the second premise using conditional elimination (→E).
  • The first premise also allows us to derive $D$ from the third premise using biconditional elimination (↔E).
  • Having $L$ we can use disjunction introduction (vI) to "or" anything to it. In particular, we "or" the $A$ that we need.
  • We have both sentences that we need on lines 5 and 6 and so we use conjunction introduction (∧I) to reach the goal of the proof.

Kevin Klement's JavaScript/PHP Fitch-style natural deduction proof editor and checker http://proofs.openlogicproject.org/

P. D. Magnus, Tim Button with additions by J. Robert Loftis remixed and revised by Aaron Thomas-Bolduc, Richard Zach, forallx Calgary Remix: An Introduction to Formal Logic, Winter 2018. http://forallx.openlogicproject.org/

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.